Binding of collagen gene products with titanium oxide. (25th February 2021) - Song, Qin; Iku, Shouhei; Sammons, Rachel; Yagami, Kimitoshi; Furusawa, Toshitake; Morimoto, Koichi; Rahaman, Md Shiblur; Kurasaki, Masaaki; Tokura, Seiichi; Kuboki, Yoshinori
Abstract: Titanium is the only metal to which osteoblasts can adhere and on which they can grow and form bone tissue in vivo, resulting in a strong bond between the implant and living bone. This discovery provides the basis for the universal medical application of Ti. However, the biochemical mechanism of bond formation is still unknown. We aimed to elucidate the mechanism of bond formation between collagen, which constitutes the main organic component of bone, and TiO2, of which the entire surface of pure Ti is composed. We analysed the binding between the soluble collagen and TiO2 by chromatography with a column packed with Ti beads of 45 µm, and we explored the association between collagen fibrils and TiO2 (anatase) powders of 0.2 µm. We ran the column of chromatography under various elution conditions. We demonstrated that there is a unique binding affinity between Ti and collagen. This binding capacity was not changed even in the presence of the dissociative solvent 2M urea, but it decreased after heat denaturation of collagen, suggesting the contribution of the triple-helical structure. We propose a possible role of periodically occurring polar amino acids and the collagen molecules in the binding with TiO2 . Graphical Abstract: